Change of salivary fluoride level with intake of fluoride releasing lozenges: A pilot study. Issue 3 (30th March 2018) - Rechmann, Peter; Rechmann, Beate M. T.; Kinsel, Richard; Featherstone, John D. B.
Abstract: Aim: Long‐term, low‐level fluoride concentrations in saliva are highly effective in caries prevention and remineralization. The aim of the present two‐phased study was to test whether fluoride‐releasing lozenges compared to placebo significantly raise salivary fluoride levels above baseline achieved by 1100 ppm fluoride toothpaste in a double‐blind, crossover pilot study. Methods: In phase 1, a four‐arm crossover basic study, four participants used one dissolvable lozenge with .25, 0.5, 1 or 1.5 mg fluoride for 1 hour. In phase 2, the three‐arm crossover main study, 11 participants used three lozenges per day for 1 hour for 1 week, establishing long‐term salivary fluoride levels dissolving 0 (control), 0.5 and 1.5 mg fluoride lozenges. Saliva was collected at baseline; during lozenge use; 5, 15, 30, and 60 minutes later; and early the next morning. Salivary fluoride levels were determined by laboratory diffusion analysis. Results: In phase 1, 5 minutes after using one lozenge, salivary fluoride levels were above baseline (0.03 ppm), reaching 0.13 ± 0.19 ppm for the 0.25 mg and 0.73 ± 0.75 ppm for the 1.5 mg fluoride lozenge, dropping to baseline after 60 minutes. In phase 2, after 1 week use of 0.5 and 1.5 mg lozenges, respectively, for the 0.5 mg lozenge for 15 minutes and the 1.5 mg lozenge 30 minutes after use, the salivary levels were significantly higher than baseline/control (0.02 ppm). During 1‐hour lozenge use, fluoride levels >0.1 ppm were consistently achieved. Conclusions: Fluoride lozenges achieved elevated salivary fluoride levels during use, but only for short periods after use.